1988
DOI: 10.1111/j.1600-0765.1988.tb01420.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ activated T lymphocytes in active versus stable periodontal lesions

Abstract: A double labeling technique was developed to detect T cell phenotype and HLA‐DR (activation) antigens on infiltrating cells in gingival biopsy sites classified as either periodontally active (≥ mm attachment loss within past 3 months), clinically similar but stable, or healthy. Serial cryostat sections were obtained from each of the above disease category biopsies in 13 periodontal maintenance patients, and were processed with sequential Leu series (T cell subsets) avidinbiotin‐peroxidase followed by anti‐HLA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…Furthermore, human T-cells displayed a reduced ability to proliferate to mitogenic stimulation after incubation with the RgpA-Kgp complex [101]. This wholesale degradation of Tcell receptors would impair T-helper and cytotoxic T-cell function at the site of infection and the number of these cells in diseased gingival tissue of periodontitis patients has been reported to be depressed [102][103][104]. Further dysregulation of the T-cell immune response by RgpA and Kgp has been suggested by Yun et al [105].…”
Section: Avoidance Of the Immune Response By P Gingivalis: Immunomentioning
confidence: 96%
“…Furthermore, human T-cells displayed a reduced ability to proliferate to mitogenic stimulation after incubation with the RgpA-Kgp complex [101]. This wholesale degradation of Tcell receptors would impair T-helper and cytotoxic T-cell function at the site of infection and the number of these cells in diseased gingival tissue of periodontitis patients has been reported to be depressed [102][103][104]. Further dysregulation of the T-cell immune response by RgpA and Kgp has been suggested by Yun et al [105].…”
Section: Avoidance Of the Immune Response By P Gingivalis: Immunomentioning
confidence: 96%
“…which are synthesized following antigenic stimulation [9]. Phenotypic analysis of T cells in periodontitis-affected tissues has demonstrated up-regulation ofthe lL-2 receptor [13] and HLA-DR [14]. a shift of CD4 and CDS populations [4.5].…”
Section: Discussionmentioning
confidence: 99%
“…The histological appearance which equates to these periods of 'active' disease in man can only be surmised. The only study attempting to quantify the functional cell types immunohistochemically during identified periods of disease activity (Reinhardt et al 1988) fails to estabhsh any clear pattern of change in T-cell types or activity amongst healthy tissue, stable lesions and active lesions and the authors do not address the fate of B-cells at all in this rigorously assessed study designed to look at T-cell kinetics. In fact, as Reinhardt hypothesises, disease activity may be reflected not in a shift of cell populations but in a switching on or switching off of cells already resident in the lesion.…”
Section: Periodontitismentioning
confidence: 99%